2019
DOI: 10.1158/1055-9965.epi-19-0023
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine Containing Aristolochic Acid and the Risk of Primary Liver Cancer in Patients with Hepatitis C Virus Infection

Abstract: Background: We investigated the association between taking herbal medicine (HM) containing aristolochic acid (AA) and the risk of primary liver cancer (PLC) among patients with hepatitis C virus (HCV) infection.Methods: This is a prospective study for the long-term followup of a nationwide population-based cohort of patients ages 18 years or older diagnosed with HCV infection during 1997 to 2010. A total of 223,467 HCV-infected patients were identified using the National Health Insurance Research Database in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 34 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Tobacco smoking and HBV infection were found to positively interact in liver carcinogenesis; 45,46 synergistic effects were also reported between tobacco smoking and chronic HCV leading to increased liver fibrosis 46,47 and increased risk of cirrhosis and HCC 46 . Exposure to aristolochic acids, widely used in traditional Chinese medicine throughout Asia, has been linked to liver cancer 48 , and a prospective study of HCV-infected patients in Taiwan has very recently reported an association between the intake of herbal medicines containing aristolochic acid and the risk of primary liver cancer 49 . Therefore, although the etiology of this disease and the role of HDV remain poorly understood, our findings suggest links between exposure to certain carcinogenic agents and HDV status in Mongolian HCC that deserve further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco smoking and HBV infection were found to positively interact in liver carcinogenesis; 45,46 synergistic effects were also reported between tobacco smoking and chronic HCV leading to increased liver fibrosis 46,47 and increased risk of cirrhosis and HCC 46 . Exposure to aristolochic acids, widely used in traditional Chinese medicine throughout Asia, has been linked to liver cancer 48 , and a prospective study of HCV-infected patients in Taiwan has very recently reported an association between the intake of herbal medicines containing aristolochic acid and the risk of primary liver cancer 49 . Therefore, although the etiology of this disease and the role of HDV remain poorly understood, our findings suggest links between exposure to certain carcinogenic agents and HDV status in Mongolian HCC that deserve further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from well-established kidney toxicity, it has recently been reported that AAs could also be closely related to the occurrence and pathogenesis of liver cancer due to their genotoxicities. 13 , 14 , 16 In this present study, for the first time, we used scRNA-seq technology to establish a high-resolution single-cell mouse liver atlas in response to AAI. As shown in the summary graphic, the molecular and cellular mechanisms of AAI-induced hepatotoxicity were reprogramed at the single-cell level (Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Herbal remedies containing AAs contribute to the risk of HCC in patients with hepatitis B or C virus infection. 14 , 15 Notably, in 2017, Ng et al . showed that AAs and their derivatives are widely implicated in liver cancers, especially in Asia, 16 where AAs quickly became the focus of public opinion, again causing widespread concern and discussion.…”
Section: Introductionmentioning
confidence: 99%
“…f., saikosaponin from Bupleurum chinense, geniposide from Gardenia jasminoides, and so on. The second class is those that might cause hepatocarcinoma in the presence of hepatitis B viruses, such as aristolochic acid from Aristolochia debilis and aflatoxin B1 from Aspergillus flavus (fungi) . Although the detailed modes of action responsible for biological damage in the liver by natural chemicals remain to be illustrated, a stringent liver safety evaluation of the drug candidates is essential.…”
Section: Toxicological Evaluation Of Natural Productsmentioning
confidence: 99%